Study of aluminum nitride formation in a plasma with effect of double laser pulses on D16T aluminum alloy in air - Trinh, Ngoc Hoang; Bazzal, Khoder; Fadaeian, A.R.; Zajogin, A.P. (Photonics Letters of Poland, 2016)
In this paper, we propose new opportunities to increase the proportion of various aluminum ions in the near-surface laser plasma in the regimes of ablation of aluminum alloy surfaces by defocused double laser pulses, and AlN nanoclusters under the sequential influence of double pulses on the target (D16T aluminum alloy). Experimental results show that the intensity of the spectral lines of Al ions reaches a maximum when the time intervals between double pulses of the order of 5÷15 us, the pulse energy of 42 mJ (Al II) and 38 mJ (Al III); The percentage of AlN nanoclusters reaches a maximum at energy of pulses of about 40 mJ, defocus of 0 mm and number of pulses of 25÷30. Full Text: PDF References Zheng Biju and Hu Wen, "A novel loss compensation technique analysis and design for 60 GHz CMOS SPDT switch*", Journal of Semicond. 37, 063003 (2016). CrossRef Perez J.A., Vera I.P., Riascos H., Caicedo J.C., "Optical emission spectroscopy of Aluminum Nitride thin films deposited by Pulsed Laser Deposition", Jornal of Physics: Conference Series 511, 1 (2014). CrossRef D.-M. Marin, F. Stokker-Cheregi, M. Dumitru, V. Ion, M. Dinescu, "Aluminium nitride thin films grown by plasma assisted pulsed laser deposition", Romanian Reports in Physics 66, 1118 (2014). DirectLink L. T. Sukhov, Laser spectral analysis (Novosibirsk 1990). Kononenko T. V., Konov V. I., Lubnin E. N., Dausinger F., "Pulsed laser deposition of hard carbon coatings at atmospheric pressure", Quantum electronics 33, 189 (2003). CrossRef Goncharov V. K., Kozadaev K. V., "Formation of the condensed phase of metals exposed to submicrosecond laser pulses", Journal of Engineering physics 83, 80 (2010). CrossRef Fadaiyan A. R., Trinh Ngoc Hoang, Zazhogin A. P., Vestnik BSU 1, 27 (2011). Fadaian A. R., Zazhogin A. P., Vestnik BSU 1, 14 (2009). Kask N. E., Michurin S. V., Fedorov G. M., "Fractal structures in a laser plume", Kvant. electron. 33, 57 (2003). DirectLink Krainov V. P., Smirnov M. B., "???????? ??????? ????????? ??? ????????? ??????????????? ???????????? ????????? ????????" Uspekhi Fizicheskikh Hauk 170, 969 (2000). CrossRef Ilin ?.P., Root L.?., Journal of science of Siberia 1, 91 (2011). Herzberg G., Electronic spectra and structure of polyatomic molecules (Mir Press 1969).